Patient exposure to X‐rays during coronary angiography and percutaneous transluminal coronary intervention: Results of a multicenter national survey. Issue 5 (6th January 2014) - Georges, Jean‐Louis; Belle, Loic; Ricard, Cécile; Cattan, Simon; Albert, Franck; Hirsch, Jean‐Lou; Monsegu, Jacques; Dibie, Alain; Khalife, Khalife; Caussin, Christophe; Maccia, Carlo; Livarek, Bernard; et al.
<x xml:space="preserve">Abstract</x> Objectives To evaluate practices for the protection from radiation of patients during coronary angiography (CA) and percutaneous coronary intervention (PCI), and to update reference values for the main radiation dose parameters. Background Few multicenter data from large populations exist on radiation doses to patients during CA and PCI. Methods RAY'ACT is a multicenter, nationwide French survey, with retrospective analysis of radiation parameters routinely registered in professional software from 33, 937 CAs and 27, 826 PCIs performed at 44 centers from January 1, through December 31, 2010. Results Kerma‐area product (KAP) was registered in 91.7% (44/48) of centers and in 91.5% of procedures for CA (median, 27.2 Gy·cm2, interquartile range [IQR], 15.5–45.2) and 91.1% for PCI (median, 56.8 Gy·cm2, IQR, 32.8–94.6). Fluoroscopy time was registered in 87.5% (42/48) of centers and in 83.1% of procedures (median, 3.7 min, IQR, 2.3–6.3 for CA; 10.3 min, 6.7–16.2 for PCI). Variability across centers was high. Old equipment and routine left ventriculography were more common and number of registered frames and frame rate were higher in centers delivering high doses. The radial route was associated with lower doses than the femoral route (median KAP 26.8 Gy·cm2 [15.1–44.25] vs. 28.1 [16.4–46.9] for CA, respectively; and 55.6 Gy·cm2 [32.2–92.1] vs. 59.4 [24.6–99.9] for PCI, respectively; P < 0.01). Conclusions This survey showed a very high rate of compliance with dose registration during CA and PCI in French nonacademic hospitals. Updated diagnostic reference values are established for the main dose parameters (KAP, 45 Gy·cm2 for CA, 95 Gy·cm2 for PCI). © 2013 Wiley Periodicals, Inc.